Comparison of mechanical property and machinability for polyetheretherketone and glass fiber–reinforced polyetheretherketone. (23rd April 2015) - Ji, Shijun; Yu, Huijuan; Zhao, Ji; Liang, Fusheng
To study and compare mechanical properties and machinability of the polyetheretherketone and the glass fiber–reinforced polyetheretherketone and analyze the relationship between the two properties, nano-indentation experiments and single-point diamond turning experiments were carried out in this article. Through nano-indentation experiments, several material characteristic parameters such as elastic modulus, hardness, and load–displacement data were obtained and load–displacement curve was drawn. It was found that the glass fiber–reinforced polyetheretherketone has higher elastic modulus and hardness but poor uniformity. By single-point diamond turning experiments, two circular planes whose materials are polyetheretherketone and glass fiber–reinforced polyetheretherketone, respectively, were machined. It was found that form accuracy (PV) and surface roughness (Ra) of the former were smaller than those of the later, and glass fiber–reinforced polyetheretherketone plane has poor machined quality. Mechanical property, including uniform structure, stiffness, and resistance to deformation, has higher influence on machining quality.